A unified framework for the multi-scale computational homogenisation of 3D-textile composites. (15th June 2019) - Ullah, Z.; Zhou, X.-Y.; Kaczmarczyk, L.; Archer, E.; McIlhagger, A.; Harkin-Jones, E.
Abstract: This paper extends the applications of a novel and fully automated multi-scale computational homogenisation framework, originally proposed by the authors (Ullah et al. (2017)) for unidirectional and 2D-textile composites, to 3D-textile composites. 3D-textile composites offer many advantages over 2D-textile composites but their highly complicated and unpredictable post-cured geometries make their design very challenging. Accurate computational models are therefore essential to the development of these materials. The computational framework described in this paper possesses a variety of novel features which have never been tried for this class of composites and can potentially help to fully automatise and improve their design process. A unified approach is used to impose the representative volume element boundary conditions, which allows convenient switching between linear displacement, uniform traction and periodic boundary conditions. The computational framework is implemented using hierarchic basis functions of arbitrary polynomial order, which allows one to increase the order of approximation without changing the finite element mesh. The yarns' principal directions, required for the transversely isotropic material model are calculated using a potential flow analysis along these yarns. This feature is very useful for 3D-textile composites and can accurately determine fibres' directions even in the case of very deformed yarns. A numerical example from literature consisting of a 3D-orthogonal woven composite is used to demonstrate the correct implementation and performance of the developed computational framework. Also, the developed computational framework is used to perform a comparative study of the homogenised mechanical properties of five 3D-textile composites with different yarn architectures.